PERFORMANCE EVALUATION OF SEED DRILL- FERTILIZER UNDER TWO DIFFERENT FARMING SYSTEMS AND TRACTOR PRACTICAL SPEEDS - Asmaa A. Alwash,; Firas Salim Al-Aani, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aim to investigate performance of seed drill - fertilizer (GIL-SAX multisem18) was evaluated under two different farming systems (till and no-till) and tractor speeds (5.28, 7.76 and 8.30 km.h-1). The characteristics were measured including draft force, wheel slip, seed delivery rate, and germination rate. The experiment was organized as a randomized complete block design (RCBD). The significant difference was examined using the least significant difference tests at a P≤0.05. The results showed a minimum draft force and wheel slip under the till system and tractor speed of 5.28 km.h-1 interaction. The lowest seed delivery rate was found when no-till was practiced with a speed of 5.28 km.h-1. Adopting the no-till system with the speed of 7.76 km.h-1 achieved the highest germination rate. The till system achieved the lowest fuel cost in economic analysis 8395 IQD. ha-1 at a speed of 8.30 km.h-1, while the no-till system achieved the lowest cost of seeds 65066 IQD. ha-1 and sowing operation cost 36079 IQD. ha-1 at speed 5.28 km.h-1. Irrigation and agronomy indicators should be addressed in the further work.